2000
DOI: 10.1017/s0022216x00005824
|View full text |Cite
|
Sign up to set email alerts
|

The Political Economy of Marine Fisheries Development in Peru, Chile and Mexico

Abstract: Latin American fish production has expanded significantly in recent years. Unfortunately, as management systems in the three major Latin American fish producing countries have not developed at the same pace, all three countries now experience problems of overfishing and industrial overcapitalisation. This article examines the distinctive national fisheries development programmes that have led to this ‘tragedy of the oceans’. By comparing and contrasting the Peruvian, Chilean and Mexican management styles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 0 publications
0
47
0
3
Order By: Relevance
“…During the last decade, the Peruvian government has enforced the law to use revenues from the anchovy fishery to cover the overall costs of fisheries management [72], regardless of the fishery involved. This applies to revenues from the auction of fishing rights for other species to international fishing fleets.…”
Section: Adaptation By Improved Monitoring and Flexible Managementmentioning
confidence: 99%
“…During the last decade, the Peruvian government has enforced the law to use revenues from the anchovy fishery to cover the overall costs of fisheries management [72], regardless of the fishery involved. This applies to revenues from the auction of fishing rights for other species to international fishing fleets.…”
Section: Adaptation By Improved Monitoring and Flexible Managementmentioning
confidence: 99%
“…For example, El Salvador is described as one of the countries making "greatest progress" in the sustainable harvesting of marine life; it also is included among those with the "most participation and commitment to international agreements and regional fish- Case studies elsewhere (e.g. Peru, Chile and Mexico) show similar changes in the fishing industry as actors adapt to declining stocks [35]. A study of fishers in Costa Rica found that recently fishers have spent more time at sea, in reaction to declining stocks [36].…”
Section: The Long Term Decline Of Fishing Returnsmentioning
confidence: 99%
“…The 1982 UN Convention on the Law of the Sea (UNCLOS) and its consolidation of Exclusive Economic Zones was an important step in reducing the severe impacts of globalised deep-sea trawling on domestic fisheries. The crisis in the Peruvian stocks in the 1970s because of state promotion of the sector and the rise in fishing effort (Ibarra et al ., 2000), also the case of the Newfoundland cod fishery and its collapse in the early 1990s, are harsh lessons from both hemispheres that highlight the dangers of weak management and raising fishing effort in a fishery beyond maximum sustainable yields.…”
Section: Policy Orientations and Management Strategiesmentioning
confidence: 99%